Knowledge, Attitude, Practice of Genotype Screening Among Undergraduate Medical Students In The University Of Abuja - Cegbeyi, Esther Malachi; Baamlong, Nicholas; Abah, Stephen (British Journal of Healthcare and Medical Research, 2024)
Background: Sickle cell disease remains the most common life-threatening genetic disorder worldwide. Globally about 312,000 children are born each year with sickle cell disease (SCD), half of which are from Nigeria[1,2,4,5,7,8]. The prevalence of sickle cell anaemia (SS) in Nigeria is estimated to be 20 per 1000 and 25% of the population have sickle trait (AS)[2,6,9,10,11]. Medical students in Nigeria are key in the future management of sickle cell disease. Therefore, it is important to understand what training in SCD is given to medical students in Nigeria and to identify any important knowledge gaps which may improve training curricula. Method: A student survey was conducted at the College of Health Sciences, University of Abuja in the Federal Capital Territory of Nigeria (FCT) in the 2021/2022 academic year. At this University, all students undergo comprehensive medical tests before admission, which include genotype screening. All medical students were eligible to complete the survey and which was advertised through year group social platforms. Data were collected using a self-administered questionnaire through Google form, after the respondent indicated their consent. The questions focused on knowledge of the disease and attitude towards genotype screening, and whether the student had undergone screening and were aware of their status. Results: In the academic year of 2021/2022 there were a total number of 374 medical students from year one to year six of these 150 (40%) completed the survey. Survey respondents included similar numbers of males and females, with a mean age of 23.7 years and were from all years of study. All the respondents had heard about sickle cell disease and 85% stated that they had attended courses which covered Sickle cell disease topics (from 63% in 1st year of study rising to over 90% by year 3). A very high proportion knew that Sickle cell disease trait can be transmitted from both parents to offspring (95%), and 90% knew that SCD can affect anyone and can occur when both parents are carriers of the Sickle gene. Fewer students (79%) knew that SCD can be diagnosed at birth. Knowledge of common symptoms for sickle cell patients was variable, while most knew that one of the most common complaints was pain in the limbs (92%), only 23% were aware that yellow eyes is also a common symptom, and 10 students (7%) incorrectly identified skin rashes as a common symptom. A total of 93% of students had been genotype-screened for SCD, and attitudes towards genotype screening, was generally positive. Most agreed that genotype screening can help prevent SCD and that pre-conception genotype screening is important. Of those who had been screened and knew their status, 68.6% were AA (adult haemoglobin without any haemoglobin disorder), 28.6% were AS (had the sickle cell trait) and 2.9% were SS (sickle cell anaemia). Conclusion: Over 90% respondents knew their sickle cell status (Hb genotype) and 2.9% had SCD (HbSS), and 29% had sickle cell trait (HbAS) consistent with consistent with the national burden in Nigeria. Reassuringly, medical students had a good knowledge of and attitude towards SCD irrespective of their year of study. Although identifying symptoms, which may be important in diagnosis, could be improved. Given that almost half of the global burden of SCD is in Nigeria, this study reflects the importance of ensuring adequate health education towards sickle cell disease among Nigerian medical students.